Особенности преподавания славянских языков в Вильнюсском университете - Коницкая, Елена; Ушинскене, Виктория (Slavistica Vilnensis, 2009)
Specificity of Slavonic Studies аt Vilnius University is expressed in the combination of well-known techniques of the traditional teaching with аn audiovisual method, and also – with more radical techniques of suggestopedy which facilitates the mastering of а teaching material аt subconscious (passive) level.